Prevalence and Correlates of Cardio-Metabolic Risk Factors Among Regular Street Food Consumers in Dar es Salaam, Tanzania - B Kagaruki G; J Mahande M; D Kimaro G; S Ngadaya E; Mayige T M; Selemani M; Jaacks LM; Jaffar S; Mfinanaga SG; Bonfoh B (Diabetes, Metabolic Syndrome and Obesity, 2021)
Gibson B Kagaruki,1,2 Michael J Mahande,2 Godfather D Kimaro,3 Esther S Ngadaya,3 Mary Mayige T,4 Majige Selemani,5 Lindsay M Jaacks,6 Shabbar Jaffar,7 Sayoki G Mfinanaga,3,8 Bassirou Bonfoh8,9 1Research Programs, National Institute for Medical Research, Tukuyu Medical Research Centre, Mbeya, Tanzania; 2Epidemiology & Biostatistics, Institute of Public Health, Kilimanjaro Christian Medical University College, Moshi, Tanzania; 3Research Programs, National Institute for Medical Research, Muhimbili Centre, Dar es Salaam, Tanzania; 4Research Programs, National Institute for Medical Research, Headquarters, Dar es Salaam, Tanzania; 5Eastern Africa Statistical Training Centre, Graduate Studies, Dar es Salaam, Tanzania; 6Global Academy of Agriculture and Food Security, The University of Edinburgh, Midlothian, UK; 7International Public Health, Liverpool School of Tropical Medicine, Liverpool, Merseyside, UK; 8Public Health Muhimbili University of Health and Allied Sciences, Dar es Salaam, Tanzania; 9Centre Suisse de Recherches Scientifiques en Côte d’Ivoire, Abdjan, Côte d’IvoireCorrespondence: Gibson B Kagaruki NIMR-Tukuyu, P.O. Box 538, Tukuyu, TanzaniaEmail gkagaruki@gmail.comBackground: Regular street food consumers (RSFCs) in Africa are at an increased risk of unhealthy eating practices, which have been associated with intermediate risk factors of cardio-metabolic diseases. However, knowledge of the magnitude and correlates of these risk factors is limited in Tanzania. This study aimed to fill this gap using data collected from RSFCs in Dar es Salaam, the largest city in Tanzania.Methodology: A cross-sectional study was carried out among 560 RSFCs in three districts of Dar es Salaam between July and September 2018. Information on socio-economic factors and demographics, behavioral risks, anthropometric and biochemical indicators was collected. Adjusted odds ratios (OR) and prevalence ratio (PR) with corresponding 95% confidence intervals (CI) were estimated using multivariable binary logistic and modified Poisson regression models, respectively.Results: On average, participants consumed 11 street food meals/week. The prevalence (95% CI) of cardio-metabolic risk factors was 63.9% (60.6– 69.9%) for overweight/obesity, 42.5% (38.3– 46.9%) for raised blood pressure, 13.5% (10.9– 16.8%) for raised triglycerides and 6.6% (4.9– 9.3%) for raised glucose levels. The correlates of overweight/obesity were female vs male sex (APR=1.3; 95% CI 1.2– 1.5), age of 41– 64 vs 25– 40 years (APR=1.4; 95% CI 1.2– 1.6), high vs low income (APR=1.2; 95% CI 1.04– 1.3), being married/cohabiting vs other (APR=1.2; 95% CI 1.01– 1.4) and family history of diabetes vs no family history (APR=1.2; 95% CI 1.01– 1.3). Age 41– 64 vs 25– 40 years, was the only significant factor associated with raised blood pressure APR (95% CI) 2.2 (1.7– 2.9) and raised glucose AOR (95% CI) 3.9 (1.5– 10.5).Conclusion: Our study revealed that RSFCs are at risk of cardio-metabolic health problems, especially women, middle-aged people and those with higher incomes. Transdisciplinary studies to understand the drivers of street food consumption are needed in order to inform interventions to mitigate the risk of developing cardio-metabolic diseases. These interventions should target both street food vendors and their consumers.Keywords: street food consumers, cardio-metabolic risks, cardio-metabolic correlates, Tanzania